Prolyl Isomerization-Mediated Conformational Changes Define ATR Subcellular Compartment-Specific Functions - Biswas, Himadri; Zhao, Shu-Jun; Makinwa, Yetunde; Bassett, James S.; Musich, Phillip R.; Liu, Jing-Yuan; Zou, Yue (Frontiers in Cell and Developmental Biology, 2022)
ATR is a PI3K-like kinase protein, regulating checkpoint responses to DNA damage and replication stress. Apart from its checkpoint function in the nucleus, ATR actively engage in antiapoptotic role at mitochondria following DNA damage. The different functions of ATR in the nucleus and cytoplasm are carried out by two prolyl isomeric forms of ATR: trans- and cis-ATR, respectively. The isomerization occurs at the Pin1 Ser428-Pro429 motif of ATR. Here we investigated the structural basis of the subcellular location-specific functions of human ATR. Using a mass spectrometry-based footprinting approach, the surface accessibility of ATR lysine residues to sulfo-NHS-LC-biotin modification was monitored and compared between the cis and the trans-isomers. We have identified two biotin-modified lysine residues, K459 and K469, within the BH3-like domain of cis-ATR that were not accessible in trans-ATR, indicating a conformational change around the BH3 domain between cis- and trans-ATR. The conformational alteration also involved the N-terminal domain and the middle HEAT domain. Moreover, experimental results from an array of complementary assays show that cis-ATR with the accessible BH3 domain was able to bind to tBid while trans-ATR could not. In addition, both cis- and trans-ATR can directly form homodimers via their C-terminal domains without ATRIP, while nuclear (trans-ATR) in the presence of ATRIP forms dimer-dimer complexes involving both N- and C-termini of ATR and ATRIP after UV. Structural characteristics around the Ser428-Pro429 motif and the BH3 domain region are also analyzed by molecular modelling and dynamics simulation. In support, cis conformation was found to be significantly more energetically favorable than trans at Ser428-Pro429 bond in a 20-aa wild-type ATR peptide. Taken together, our results suggest that the isomerization-induced structural changes of ATR define both its subcellular location and compartment-specific functions and plays an essential role in promoting cell survival and DNA damage responses.